Stable intelligent Controller Design for Generalized Flow Shop Systems - Reza Ghasemi (Institute of Advanced Engineering and Science, 2013)
Designing a stable fuzzy controller for a class of generalized flow shop systems is addressed in this paper based on max-plus algebra. The proposed controller is multi-input single-output. Robustness against uncertainties in the service times, stabilizing the closed loop system and withholding the blocking effect are the main properties of the proposed controller. An illustrative example is given to show the effectiveness of the proposed method.DOI: http://dx.doi.org/10.11591/ij-ai.v2i2.1325